Organizational and technological aspects of industrial facility renovation - Zilberova Inna; Mailyan Vadim; Novoselova Irina; Petrov Konstantin (E3S Web of Conferences, 2023)
The refurbishment of industrial structures is a multifaceted, resource-intensive, and financially demanding undertaking. The process entails various challenges that necessitate thorough consideration during the design phase. Such an approach is pivotal in devising effective solutions for the reconstruction of industrial facilities, regardless of the operational conditions, and can lead to substantial reductions in construction costs. The ultimate objective of such renovation endeavors is to enhance production capacity and overall enterprise profitability, mitigate adverse environmental effects, and ameliorate the quality of urban living environments.